Connecting the experiences of persons with disabilities and social workers in Nigerian care institutions regarding COVID-19 vaccine uptake: a qualitative descriptive-interpretive design - Farah Naz Rahman; Farah Naz Rahman; Anthony Obinna Iwuagwu; Christopher Ndubuisi Ngwu; Michael Ebe Kalu; Amani Kasherwa; Mohammad Rocky Khan Chowdhury; Manzur Kader (Frontiers Media S.A., 2024)
BackgroundDuring the COVID-19 pandemic, persons with disabilities (PWDs) have faced additional disadvantages that have exacerbated their physical and mental health challenges. In Nigeria, where cultural, religious, and informational barriers persist, understanding these factors is critical for improving health interventions, including vaccine uptake among PWDs.MethodsThis study employed a qualitative descriptive-interpretive design to explore the perceptions of PWDs regarding the COVID-19 pandemic and the vaccine, alongside social workers' views on their roles in facilitating vaccine uptake. We conducted in-depth semi-structured telephone interviews with 20 participants, comprising 16 PWDs and four social workers in Nigerian rehabilitation homes. Data were analyzed using critical thematic analysis to identify key themes influencing attitudes toward the pandemic and vaccine uptake.ResultsThe study uncovered significant barriers to COVID-19 vaccine uptake among PWDs, primarily driven by mistrust in government initiatives, widespread conspiracy theories, and deeply held cultural and religious beliefs. Additionally, while social workers played crucial roles as community surveillance officers, in-house educators, and community referral agents, their interventions lacked specific strategies aimed at increasing vaccine uptake among PWDs. Their efforts were more focused on addressing the psychological impacts of the pandemic rather than fostering behavioral changes toward vaccine acceptance.ConclusionTo enhance COVID-19 vaccine uptake among PWDs in Nigerian rehabilitation homes, targeted interventions that address the identified barriers are essential. These should include trust-building measures, culturally and religiously sensitive communication strategies, and tailored educational programs by social workers. Moreover, training social workers in specific, evidence-based strategies to increase vaccine uptake is crucial for mitigating the pandemic's impact on this vulnerable population.